AN ANALYSIS OF PERSONALITY TRAITS IN UNDERGRADUATE DOCTOR OF PHYSICAL THERAPY STUDENTS AT THE INSTITUTE OF PHYSICAL MEDICINE AND REHABILITATION AND REHMAN COLLEGE OF REHABILITATION SCIENCES: A CROSS-SECTIONAL STUDY - Qazi, Minahil; Amin, Faraz; Samin, Alina Rashid; Hussain, Sara; Ali, Menahil; Kakar, Hoor Ali (Annals of Allied Health Sciences, 2024)
Objective: To determine personality traits among undergraduate Doctor of Physical Therapy (DPT) students, find its association with demographics (age, institute, gender, residence, financial status), and CGPA. Material & Methods: This study was a cross-sectional study, in which 209 participants were recruited from IPM&R and RCRS and convenience sampling was used for data collection. SPSS (Statistical Package for the Social Sciences) version 2022 was used for the analysis of the data. Results: The personality trait calculated for 209 participants lies within the normal range of their respective domains with the exception of demographic factors such as institute and CGPA, which demonstrated no significant associations with personality traits. Notably, a positive correlation was observed between openness to experience and extraversion with CGPA, while a negative correlation was established between agreeableness, conscientiousness, and emotional stability with CGPA. Conclusion: From the present study, we conclude that in majority of the undergraduate student’s personality traits were within the normal score while association of personality traits with their demographics clearly showed that agreeableness, extraversion and emotional stability was closely associated with all the demographics except that of institutions and CGPA. While a positive correlation of CGPA existed with openness to experience and extraversion while a negative correlation